THE EFFECT OF REPETITIVE METAL CASTING ON THE TENSILE STRENGTH OF DENTURES - Sri Wiwik Wiyanti; Mujiwati Mujiwati; Adi Wibowo, Sambodo; Marzia M. Tetelepta; Imas Maesaroh (Journal of Vocational Health Studies, 2024)
Background: Dentures or prostheses function to replace chewing and dental arch structures. Denture plates used in dentistry are made with acrylic resin, metal, or a combination of acrylic and metal. Metals are shiny, opaque chemical substances and good conductors of heat and can be polished. Recycling or reusing used metal is an option in making prostheses because the price of new metal is increasing, and metal recycling is quite effective. Purpose: To determine the effect of repeated metal casting on the strength of the metal frame denture base. Method: The current research is a laboratory study with a tensile test in the form of dumbbells with iso 22674 with a length of 15 ± 1 mm and a diameter of 3 ± 1 mm. This research used 18 CoCr metal samples divided into three groups, namely 100% new metal group (control), 50% new + 50% repeated composition group, and 100% repeated group. Result: The mean strain of the new 100% CoCr metals group was 0.133%, strain mean of the new 50% CoCr + 50% repeated metals group was 0.1%, and the strain of the 100% repeated CoCr metals group was 0.066%. The average modulus of elasticity (MPa) for the new 100% CoCr metals group is 7866, or 711 MPa, the new 50% CoCr + 50% repeat metals group is 7538, or 833 MPa, the 100% CoCr metals group is 6659, or 336 MPa. Conclusion: The new 100% CoCr metal group has a higher average tensile strength value than the 50% new CoCr metal + 50% repeated group, and the lowest is the 100% repeated CoCr metal group.